Tendencje zmian w rozwoju fizycznym dzieci i młodzieży wiejskiej Ziemi Lubuskiej w wieku 7-18 lat = Change tendencies in the physical development of children and rural youth aged 7-18 in the Lubusz Land - Asienkiewicz, Ryszard; Tatarczuk, Józef (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the study was to show change directions in the physical development of children and school youth in the Lubuskie Voivodeship between 2002 and 2017. The study material was gathered between 2015 and 2018 among 3996 pupils (1858 boys and 2138 girls) from rural areas, ages 7-18, in randomly selected primary, junior high school, and secondary schools. The Martin technique was used to measure the height and body mass of the children and youth, on the basis of which the mass and height index (Rohrer`s index) was calculated.
Keywords: trend sekularny; rozwój fizyczny; środowisko wiejskie; dzieci i młodzież szkolna; charakterystyka porównawcza; secular trend; physical development; rural environment; children and school youth; comparative characteristics